A Connexin Gene (GJB3) Mutation in a Chinese Family With Erythrokeratodermia Variabilis, Ichthyosis and Nonsyndromic Hearing Loss: Case Report and Mutations Update - Gao, Yajuan; Zhang, Qianli; Zhang, Shiyu; Yang, Lu; Liu, Yaping; Liu, Yuehua; Wang, Tao (Frontiers in Genetics, 2022)
Background Gap junctions formed by connexins are channels on cytoplasm functioning in ion recycling and homeostasis. Some members of connexin family including connexin 31 are significant components in human skin and cochlea. In clinic, mutations of connexin 31 have been revealed as the cause of a rare hereditary skin disease called erythrokeratodermia variabilis (EKV) and non-syndromic hearing loss (NSHL). Objective To determine the underlying genetic cause of EKV, ichthyosis and NSHL in three members of a Chinese pedigree and skin histologic characteristics of the EKV patient. Methods By performing whole exome sequencing (WES), Sanger sequencing and skin biopsy, we demonstrate a Chinese pedigree carrying a novel mutation of GJB3 with three patients separately diagnosed with EKV, ichthyosis and NSHL. Results The proband, a 6-year-old Chinese girl, presented with demarcated annular red-brown plaques and hyperkeratotic scaly patches on her trunk and limbs. Her mother has ichthyosis with hyperkeratosis and geographic tongue while her younger brother had NSHL since birth. Mutation analysis revealed all of them carried a novel heterozygous missense mutation c.293G>A of GJB3. Skin biopsy showed many grain cells with dyskeratosis in the granular layer. Acanthosis, papillomatosis, and a mild superficial perivascular lymphocytic infiltrate were observed. Conclusion A novel mutation of GJB3 associated with EKV, ichthyosis and NSHL is reported in this case. The daughter with EKV and the son with NSHL in this Chinese family inherited the mutation from their mother with ichthyosis. The variation of clinical features may involve with genetic, epigenetic and environmental factors.